2015
DOI: 10.1177/1740774515594362
|View full text |Cite
|
Sign up to set email alerts
|

Informed consent in clinical research: Consensus recommendations for reform identified by an expert interview panel

Abstract: BackgroundInformed consent is the cornerstone for protection of human subjects in clinical trials. However, a growing body of evidence suggests that reform of the informed consent process in the United States is needed.MethodsThe Clinical Trials Transformation Initiative conducted interviews with 25 experienced observers of the informed consent process to identify limitations and actionable recommendations for change.ResultsThere was broad consensus that current practices often fail to meet the ethical obligat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 6 publications
3
41
0
1
Order By: Relevance
“…As in our study, other research has found (Cortes et al 2010)—and indeed there seems to be consensus (Lorell et al 2015)—that the leading problem regarding informed consent is the length and amount of information included in informed consent documents. However, much of this information is critical.…”
Section: Discussionsupporting
confidence: 84%
“…As in our study, other research has found (Cortes et al 2010)—and indeed there seems to be consensus (Lorell et al 2015)—that the leading problem regarding informed consent is the length and amount of information included in informed consent documents. However, much of this information is critical.…”
Section: Discussionsupporting
confidence: 84%
“…It is anticipated that the role for multimedia in the consent process will become more common as nearly 90% of the United States population regularly uses the internet and media-based technology costs continue to decrease and become more portable [18, 57]. Therefore, it is critical that the development of new electronic consent tools be integrated with a cognitive approach to improve learning and rigorously tested in clinical trials to evaluate effects on comprehension [58]. …”
Section: Discussionmentioning
confidence: 99%
“…suggest changing the guideline to permit trial inclusion of children without a legally acceptable representative . The length and technical language of the consent form is a highly debated topic in both the north and south, as is the view that its content serves mainly to protect sponsors .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kalabuanga et al suggest changing the guideline to permit trial inclusion of children without a legally acceptable representative [33]. The length and technical language of the consent form is a highly debated topic in both the north and south, as is the view that its content serves mainly to protect sponsors [32,34]. Based on the results and the discussion in the previous paragraph, some interviewees seemed unaware that GCP as a guideline allows for an adapted application.…”
Section: Discussionmentioning
confidence: 99%